1984
DOI: 10.1038/bjc.1984.254
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cancer antigen CA125: a prospective clinical assessment of its role as a tumour marker

Abstract: Summary Serum CA 125, quantified by an immunoradiometric assay employing the monoclonal antibody OC125 was found to be elevated in 48/58 (83%) of patients with established ovarian cancer. All histological types of carcinoma were antigen positive and there was a positive correlation between the frequency and level of serum CA125 and body burden of tumour. Twenty patients undergoing chemotherapy had serial CA125 estimations following a prospective protocol. Variation in CA125 level reflected disease progression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
134
0
5

Year Published

1986
1986
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 304 publications
(147 citation statements)
references
References 10 publications
8
134
0
5
Order By: Relevance
“…Correlation with clinical course of disease (Table IV; Figure la- This study confirms the previously demonstrated utility of CA 125 as a marker in ovarian cancer (Bast et al, 1983;Canney et al, 1984 Patients with high levels of PLAP had a poor prognosis in agreement with previous studies (Doellgast & Homesley, 1984). These differences may reflect cellular heterogeneity within a tumour either in terms of sensitivity to therapy or in terms of cell loss mechanisms.…”
Section: Patientssupporting
confidence: 80%
See 2 more Smart Citations
“…Correlation with clinical course of disease (Table IV; Figure la- This study confirms the previously demonstrated utility of CA 125 as a marker in ovarian cancer (Bast et al, 1983;Canney et al, 1984 Patients with high levels of PLAP had a poor prognosis in agreement with previous studies (Doellgast & Homesley, 1984). These differences may reflect cellular heterogeneity within a tumour either in terms of sensitivity to therapy or in terms of cell loss mechanisms.…”
Section: Patientssupporting
confidence: 80%
“…Chemotherapy schedules and patient assessment were as previously reported (Canney et al, 1984 globule. The mouse used for the development of HMFG2 also received cultured milk epithelial cells (Arklie et al, 1981).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity of serum CA 125 for pretreatment ovarian carcinoma varied from 43%-97% depending on the stage of ovarian malignancy. The progressive increase of sensitivity was observed from stage I to stage IV (stage 1:43%, stage I1: 85%, stage II1: 93%, stage IV: 97%, overall sensitivity for all stages : 82%) thus reflecting that the sensitivity increases with advancing stage of malignancy (18)(19)(20)(21)(22). In addition, this marker is also reported to be elevated in malignancies of breast (17.6%), colorectal (15.1%), gastric (30.9%), esophagus (10.5%), liver (49%), biliary tract (45.8%), pancreas (52.6%), lung (29.5%), and endometrium (31.8%).…”
Section: Cancer Antigen 125 (Ca 125)mentioning
confidence: 99%
“…An immunoradiometric assay has been developed to measure the concentrations of CA125 . High concentrations of CA125 have been found in more than 80 percent of sera from patients with ovarian cancer, and the test is especially promising in the follow-up of these patients Canney et al, 1984). Elevated serum CA125 levels have also been found in patients with various gastrointestinal cancers, especially in patients with pancreatic cancer (59%) Klug et al, 1984).…”
mentioning
confidence: 96%